Organocatalyzed Glycosylation for the Stereoselective Synthesis of O/C-Glycosides - Dubey, Shashiprabha; Mandal, Pintu Kumar (Synlett, 2025)
Oligosaccharides play a pivotal role in biological systems and support immune function due to their unique sugar structures. For a better understanding of the biochemical processes, it is essential to need pure and structurally well-defined oligosaccharides. Even though there has been significant progress in the synthesis of oligosaccharides, the efficient and stereoselective synthesis of glycosidic bonds through chemical glycosylation remains a challenging task for chemists. Organocatalysis is an exciting field in chemistry that utilizes small organic molecules as catalysts to accelerate chemical reactions under substoichiometric conditions. These catalysts offer advantages like environmentally friendly conditions, high selectivity, and efficiency for synthesizing complex molecules. In the last few years, organocatalyzed glycosylation has significantly progressed in carbohydrate chemistry particular to the stereoselective synthesis of oligosaccharides. This personal account describes the organocatalytic glycosylation methodologies developed by our group for activation of trichloroacetimidate donor and glycal substrates resulting in the specific formation of α- or β-glycosidic bonds.1 Introduction2 Trichloroacetimidate Donor3 Glycals4 Conclusion
Keywords: organocatalysis; glycosylation; catalyst; stereoselectivity; oligosaccharides